The concept of negritude in the poetry of Léopold Sédar Senghor - Bâ, Sylvia Washington, 1937- (Princeton, New Jersey : Princeton University Press, 1973)
Negritude has been defined by Léopold Sédar Senghor as "the sum of the cultural values of the black world as they are expressed in the life, the institutions, and the works of black men." Sylvia Washington Bâ analyzes Senghor's poetry to show how the concept of negritude infuses it at every level. A biographical sketch describes his childhood in Senegal, his distinguished academic career in France, and his election as President of Senegal.Themes of alienation and exile pervade Senghor's poetry, but it was by the opposition of his sensitivity and values to those of Europe that he was able to formulate his credo. Its key theme, and the supreme value of black African civilization, is the concept of life forces, which are not attributes or accidents of being, but the very essence of being. Life is an essentially dynamic mode of being for the black African, and it has been Senghor's achievement to communicate African intensity and vitality through his use of the nuances, subtleties, and sonorities of the French language.In the final chapter Sylvia Washington Bâ discusses the future of Senghor's belief that the black man's culture should be recognized as valid not simply as a matter of human justice, but because the values of negritude could be instrumental in the reintegration of positive values into western civilization and the reorientation of contemporary man toward life and love.Originally published in 1973.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Préface -- Table of Contents -- Chapter I. From the Sine to the Seine -- Chapter II. The Experience of Negritude: Exile and the Kingdom -- Chapter III. The Basis of Negritude: Black African Ontology -- Chapter IV. The Expression of Negritude: Black African PsychophysioIogy -- Chapter V. The Fundamental Traits of Negritude: Rhythm and Imagery -- Chapter VI. The Future of Negritude: The "Civilization of the Universal" -- Translations of Selected Poems -- Glossary -- Bibliography -- Index -- Backmatter
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Senghor, Léopold Sédar, -- 1906-2001 -- Criticism and interpretation; Senghor, Leopold Sedar, -- 1906-2001 -- Criticism and interpretation; Senghor, Léopold Sédar, -- 1906-2001; Senegalese poetry (French) -- History and criticism; Negritude (Literary movement); Black people -- Race identity; Poésie sénégalaise (française) -- Histoire et critique; Négritude.; Personnes noires -- Identité ethnique; POETRY -- American -- African American; POETRY -- Continental European; Black people -- Race identity; Negritude (Literary movement); Senegalese poetry (French); Criticism, interpretation, etc